2006
DOI: 10.1016/j.soilbio.2006.04.042
|View full text |Cite
|
Sign up to set email alerts
|

Soil microbial and nutrient dynamics in a wet Arctic sedge meadow in late winter and early spring

Abstract: Microbial activity is known to continue during the winter months in cold alpine and Arctic soils often resulting in high microbial biomass. Complex soil nutrient dynamics characterize the transition when soil temperatures approach and exceed 0 °C in spring. At the time of this transition in alphine soils microbial biomass declines dramatically together with soil pools of available nutrients. This pattern of change characterizes alpine soils at the winter-spring transition but whether a similar pattern occurs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
115
3
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(133 citation statements)
references
References 56 publications
(76 reference statements)
11
115
3
2
Order By: Relevance
“…1 and 2) are similar to the responses of Arctic and alpine species studied by Jaeger et al (1999) and Jonasson et al (1999) to additions of nutrients. Soil microorganisms do not appear to be able to compete effectively for N early in the season, possibly because of the low amount of microbial biomass following the late winter decline due to the lack of labile carbon (Schimel and Clein 1996;Jaeger et al 1999;Bardgett et al 2005;Edwards et al 2006). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 and 2) are similar to the responses of Arctic and alpine species studied by Jaeger et al (1999) and Jonasson et al (1999) to additions of nutrients. Soil microorganisms do not appear to be able to compete effectively for N early in the season, possibly because of the low amount of microbial biomass following the late winter decline due to the lack of labile carbon (Schimel and Clein 1996;Jaeger et al 1999;Bardgett et al 2005;Edwards et al 2006). …”
Section: Discussionmentioning
confidence: 99%
“…In contrast, microbes continue to show active growth in the autumn and winter months in alpine and some Arctic soils (Clein and Schimel 1995;Hobbie and Chapin 1996;Brooks et al 1996Brooks et al , 1998Grogan and Jonasson 2006;Nobrega and Grogan 2007). Peak annual microbial biomass with slow N turnover rates occurs in late winter (Schimel et al 2004;Schmidt and Lipson 2004;Edwards et al 2006;Buckeridge and Jefferies 2007). Nutrients released from cells of senescing microbes when soil temperatures rise in late winter and spring may represent the largest single annual input of available N into these cold soils (Jaeger et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…While the growing season presents opportunity to investigate the most productive time for these ecosystems, it might not be a good way to study annual carbon fluxes. Research through snow manipulation has shown that previous seasons' winter and spring climatic events play a role in summer and year-long growth (Robinson, 2002;Aerts et al, 2005;Edwards et al, 2006). Edwards et al (2006) found peak nutrient availability to be early in the freeze-thaw period when soil temperatures were 25 between -7 and 0°C; as such, solely measuring growing season nutrient availability does not encompass the period when soil-available nutrients may be at their peak.…”
Section: Comparing the Influence Of Abiotic Conditions And Nitrogen Amentioning
confidence: 99%
“…Mikan et al (2002) found that warming in laboratory incubation studies stimulated microbial activity and increased nutrient turnover in thawed soils. Microbial activity is known to remain active throughout the winter season and can have significant 30 contributions to nutrient budgets during spring thaw (Hobbie and Chapin, 1996;Schmidt and Lipson, 2004;Edwards et al, 2006). Because the insulating snow layer prevents Arctic mid-winter soils from falling below -10°C (Clein and Schimel, 1995), the occurrence of freeze-thaw events allows microorganisms to remain active as long as pockets of liquid water are still present as a result of the snow insulation (Edwards et al, 2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation